تأثير مسحوق ثمار وأوراق نبات الحنظل Citrullus colocynthis (L.)Schrad. في بعض جوانب حياتية ذبابة الدودة الحلزونية للعالم القديم Chrysomya bezziana (Diptera:Calliphoridae) - حسـن سهـاد حميـد (Al-Nahrain Journal of Science, 2018)
This study was made to test the effectiveness of Citrullus colocynthis fruits and leaves powders in respect of biological performance aspect of the Old World Screw -Worm Fly Chrysomya bezziana as (mortality and pupal weights). The results showed that the powders which used have clear effectiveness in all factors selected and the powder of fruits was more active than leaves powder. Higher eggs mortality rates were 34.28 % at (2:5) concentration of fruits powder and higher mortality rates were the first, second, and third larval instars were (62.94,48.94,35.92%) respectively in the same treatment and concentration. Also, the results appeared there was negative correlation relationship between concentrations of powders and pupal weights, however, the pupal weights decreased to 21.2 mg at (2:5)g concentration of fruits powder compared with 43.6 mg of the control.